GROWTH PERFORMANCE OF CHLORELLA SPP. IN DIFFERENT WATER CONDITIONS AS CULTURE MEDIA - Delan, Gloria; Bernante, Servano V; Pepito, Ador R; Lamayo, Ma. Helian A; Bontia, Presentation V; Juntilla, Ursina S; Camongay, Maximo L (Journal of Agriculture and Technology Management, 2015)
Chlorella is a spherical, single cell green algae belonging to phylum Chlorophyta. It multiplies rapidly, requiring only carbon dioxide, water, sunlight, and a small amount of minerals to reproduce. This study was conducted to determine the growth performance of Chlorella spp. in different water conditions as culture media. Chlorella was cultured using empty glass bottles provided with aeration to have a steady supply of oxygen. There were three treatments with three replications in a Randomized Complete Block Design (RCBD) which include sterilized seawater as Treatment 1 (T1); non-sterilized seawater as Treatment 2 (T2); and tilapia pond water as Treatment 3 (T3). All the culture media were fertilized with ammonium, urea, and phosphate after the inoculation of cells. Counting of Chlorella cells was done daily and the different water parameters were monitored twice a day. Results revealed that there is significant difference among the growth of Chlorella in three treatments (Fc= 7.09; Ft = 3.3) using ANOVA at 5% level of significance. On further analysis through DMRT, results revealed that T1 (sterilized seawater) and T3 (Tilapia pond water) have no significant difference from T2 (non-sterilized seawater). Result of the study shows that tilapia pond water can be a potential medium for Chlorella production for the possible supply of Chlorella for other industrial endeavors.